Retracted: Effects of cardiac resynchronization therapy in patients with inotrope‐dependent class IV end‐stage heart failure. Issue 6 (2nd July 2013) - Nakajima, Ikutaro; Noda, Takashi; Kanzaki, Hideaki; Ishibashi, Kohei; Miyamoto, Koji; Yamada, Yuko; Okamura, Hideo; Satomi, Kazuhiro; Aiba, Takeshi; Kamakura, Shiro; Anzai, Toshihisa; Ishihara, Masaharu; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) has been widely used for the treatment of refractory heart failure (HF). However, the efficacy of CRT is not well established in class IV HF patients on inotropic support. Methods: Twenty‐six patients (age 55±18 years, 73% men) with inotrope‐dependent HF were reviewed to evaluate the effectiveness of CRT in class IV HF patients on inotropic support. Results: Intravenous inotropic therapy was administered for 72±56 days before CRT and consisted of dobutamine ( n =24; 3.0±1.2 μg kg −1 min −1 ), dopamine ( n =2; 4.5±2.1 μg kg −1 min −1 ), and/or milrinone ( n =16; 0.12±0.09 μg kg −1 min −1 ). CRT did not produce significant reverse remodeling in eligible patients (left ventricular ejection fraction 23±7% to 25±9%; p =0.23, left ventricular end‐diastolic diameter 70±9 mm to 68±9 mm; p =0.14). After CRT device implantation, 13 (50%) patients experienced 1 or more episodes of ventricular tachyarrhythmia or sudden cardiac death. Twenty (77%) patients survived to hospital discharge with weaning from inotropic support (70±70 days after CRT implantation). The 1‐year survival rate was 81%. However, data from long‐term follow‐up showed that 68% of the study patients who attained survival discharge had an HF hospitalization event within the follow‐up period. Conclusion: CRT did not result in significant reverse remodeling in patients with inotrope‐dependent class IV end‐stage HF. However, it contributed to dramatically improve the cardiovascular outcomes at least in the short‐term period in some patients.